The Effect of Five-Finger Relaxation Technique to The Sleep Quality of Breast Cancer Patients - Rosliana Dewi; Laili Rahayuwati; Titis Kurniawan (Jurnal Keperawatan Padjadjaran, 2018)
Sleeping disorder is a symptom often suffered by breast cancer patients. To overcome it, five-finger relaxation technique is considered helpful. In previous research, this technique can be utilized to lower the level of anxiety and fatigue. This research, therefore, aims at identifying the effect of five-finger relaxation technique to the sleep quality of breast cancer patients.The research method used that of quasi experiment with pre-test and post-test control group design. The population included breast cancer patients within the service of the healthcare in Sekarwangi Hospital and R. Syamsudin SH Hospital. Sampling was done consecutively. The number of samples from control and intervention group were 30 people each. The intervention group received a standard hospital therapy and five-finger relaxation technique divided in 15 sessions with 10-15 minutes time every other day for 1 month. Meanwhile, the control group received only a standard hospital therapy. The measurement tool was PSQI. The analysis used paired sample t-test and independent sample t-test.The result of the research has shown a difference in scores during pre-test and post-test of the sleep quality on both groups due to p value < 0.05. A difference has striken on the scores of sleep quality between control and intervention group with the latter having higher scores than the former.It can be concluded that five-finger relaxation technique does affect the quality sleep of breast cancer patients. The result of this research can be an additional intervention to decrease the symptoms suffered by breast cancer patients.